Zinka Zorko (24. februar 1936–22. marec 2019): Besede slovesa - Orožen, Martina (Slavia Centralis, 2020)
Martina Orožen dedicates words of farewell to academician dr. Zinka Zorko, Professor Emeritus of the University of Maribor and full member of the Slovenian Academy of Sciences and Arts.